God's library: the archaeology of the earliest Christian manuscripts - Nongbri, Brent (Yale University Press, 2018)
Cover -- Halt Title -- Title -- Copyright -- Contents -- Acknowledgments -- Map Showing Locations in Egypt -- PROLOGUE Reintroducing the Earliest Christian Manuscripts -- 1. The Early Christian Book -- 2. The Dating Game -- 3. Finding Early Christian Books in Egypt -- 4. A Discovery "Which Threw All Others in the Shade": The Beatty Biblical Papyri -- 5. An Elusive Collection: The Bodmer Papyri -- 6. Excavating Christian Litter and Literature at Oxyrhynchus -- 7. Fabricating a Second-Century Codex of the Four Gospels -- EPILOGUE The Future of Ancient Christian Books -- Appendix: Christian Books from Oxyrhynchus -- Notes -- Bibliography -- Index of Subjects -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Z -- Index of Manuscripts -- A -- B -- C -- F -- G -- H -- J -- L -- M -- N -- O -- P -- Q -- S -- T -- X -- Z